2015
DOI: 10.1080/00401706.2013.872700
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Envelopes for Multivariate Linear Regression

Abstract: We introduce envelopes for simultaneously reducing the predictors and the responses in multivariate linear regression, so the regression then depends only on estimated linear combinations of X and Y. We use a likelihood-based objective function for estimating envelopes and then propose algorithms for estimation of a simultaneous envelope as well as for basic Grassmann manifold optimization. The asymptotic properties of the resulting estimator are studied under normality and extended to general distributions. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…We therefore refer to the RRR model as fully supervised. The SupSVD model (2) is also connected with the envelope model that was recently proposed by Cook et al [8] and further developed in [32,7,11,10]. The envelope model is a parsimonious model for multivariate regression that is based on the assumption that variation in the response can be divided into two parts: a material part that is related to the predictor, and ) -an immaterial part that is unrelated to the predictor.…”
Section: Connections With Existing Modelsmentioning
confidence: 99%
“…We therefore refer to the RRR model as fully supervised. The SupSVD model (2) is also connected with the envelope model that was recently proposed by Cook et al [8] and further developed in [32,7,11,10]. The envelope model is a parsimonious model for multivariate regression that is based on the assumption that variation in the response can be divided into two parts: a material part that is related to the predictor, and ) -an immaterial part that is unrelated to the predictor.…”
Section: Connections With Existing Modelsmentioning
confidence: 99%
“…They also showed that asymptotically the envelope estimatorβ is always better than the standard maximum likelihood estimator b. In other work, simultaneous envelopes (Cook & Zhang, 2015b) allow for simultaneously reducing the response and random predictor vectors.…”
Section: Model For Predictor Envelopesmentioning
confidence: 96%
“…Recent developments of envelopes under other settings may be found in, for example, Su and Cook (), Cook et al . () and Cook and Zhang (). In particular, Cook and Zhang () studied the relationship between envelopes and canonical correlation analysis.…”
Section: Review Of Envelopesmentioning
confidence: 98%
“…() and Cook and Zhang (). In particular, Cook and Zhang () studied the relationship between envelopes and canonical correlation analysis. They concluded that, although there is a weak population connection, canonical correlation analysis is not well suited as a basis for envelope methodology.…”
Section: Review Of Envelopesmentioning
confidence: 99%